Improvement of energy performance indicator for buildings in Malaysia - Ponichan, Hairi (2019)
Buildings are the leading energy consuming sectors that represents 40% of the global energy consumption. The building energy performance indicator is a comparative measurement indicator. More than 53 building energy performance indicator exists with various key performance indicators and methodological approaches. The objective of this research is to propose an improved methodology approaches and obtained an improved energy performance indicator for buildings in Malaysia. Upon data collection and analysis, building samples are analyze using three (3) parameters. These parameters are building categories, net floor area and building energy consumption. In addition, the building samples and reference buildings will be accessed and calculated based on similar climate and building function in order to produce a relatively consistent with less significant disparity results. Finding indicate 18 buildings out of 55 Land Plots that fulfilled overall improved requirements of building energy performance indicator. The building energy consumption that fulfilled the overall requirement is regressed against net floor area. As a result, a linear regression graph and variance value is produced. The early result indicates that the overall building energy performance indicator value of 153.2 kWh/m².year with unsatisfying R2 of 0.278. Thus, an addition requirement will be imposed which is the data will be comparing based on United States (Star, 2014) Primary Function compared to KETTHA Guideline for Energy Efficiency in Buildings dan GBI Malaysia existing building energy performance indicator. The result indicates building energy performance indicator of 137.0kWh/m².year with satisfying R2 of 0.910 for office building. The result is specifically compared with three (3) reference buildings that which are Wisma Rozali, Wisma Sunway and Menara Persekutuan Melaka. The result verification is -8.27%, +12.71 and a merely 2.02% respectively. The results conclude that sample buildings that passed improved parameter assessment method are more credible. While, improved building energy performance indicator method finding result a stunning value of 137kWh/m2.year when compared to the KETTHA propose standard case building energy performance indicator. The result reflected that improved building energy performance indicator is in line with previous Malaysia study on building energy performance indicator to a certain extend.